2015
DOI: 10.1186/s40064-015-1164-7
|View full text |Cite
|
Sign up to set email alerts
|

The rs10993994 in the proximal MSMB promoter region is a functional polymorphism in Asian Indian subjects

Abstract: BackgroundThe microseminoprotein gene encoding prostate secretory protein of 94 amino acids (PSP94) harbours a potential risk allele (rs10993994) for prostate cancer (PCa) in its promoter region. However, studies on rs10993994 have been sparse in Asian Indians.MethodsThe present study recruited a sample population of 44 benign prostatic hyperplasia patients, 33 PCa patients and 60 healthy participants, of which, participants without other confounding risk factors for PCa were retained. The serum PSP94 (sPSP94)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Nonetheless, three large functional studies show that the T allele at rs10993994 is associated with lower sPSP94 levels as compared to the C allele, in PCa cases (69) as well as healthy controls (70,71). Our study also showed the T risk allele to be associated with reduced PSP94 mRNA and protein expression, in both malignant and non-malignant cases and the rs10993994 was found to be a functional SNP in Asian Indians (64). Nevertheless, rs10993994 had been shown to be associated with both the altered sPSP94 expression and PCa risk (69,72).…”
Section: Psp94 Gene Variants and Their Significance In Prostate Tumorsupporting
confidence: 51%
See 2 more Smart Citations
“…Nonetheless, three large functional studies show that the T allele at rs10993994 is associated with lower sPSP94 levels as compared to the C allele, in PCa cases (69) as well as healthy controls (70,71). Our study also showed the T risk allele to be associated with reduced PSP94 mRNA and protein expression, in both malignant and non-malignant cases and the rs10993994 was found to be a functional SNP in Asian Indians (64). Nevertheless, rs10993994 had been shown to be associated with both the altered sPSP94 expression and PCa risk (69,72).…”
Section: Psp94 Gene Variants and Their Significance In Prostate Tumorsupporting
confidence: 51%
“…Also, this SNP was not found to be a predisposing factor for BPH development (62,63). In a recent study by our group, we observed that the frequency of rs10993994 was similar in healthy participants as well as BPH and PCa patients (64). Another Asian study, which included 122 PCa patients from North India, suggested that the T risk allele was associated with risk for metastatic PCa (65).…”
Section: Psp94 Gene Variants and Their Significance In Prostate Tumormentioning
confidence: 65%
See 1 more Smart Citation
“…28,30 As found in previous studies in men of African ancestry, 16 directional consistency was also observed for the majority (>80%) of risk variants in Latinos, among which~30% were nominally statistically significant, suggesting that most of the known genetic susceptibility loci for PrCa generalize to the Latino population, which may not be surprising given their high degree of European ancestry. At 10q11.22, the risk variant rs10993994 has been consistently associated with PrCa risk across populations, [32][33][34] and is likely to be the putative causal variant within the region. The risk region at 8q24 harbors multiple independent risk variants and is consistently recognized as the most significant PrCa risk region across ethnic populations.…”
Section: Discussionmentioning
confidence: 99%
“…16,31 However, in the Latino population, the 10q11.22 surpassed 8q24 as the most significant risk region. At 10q11.22, the risk variant rs10993994 has been consistently associated with PrCa risk across populations, [32][33][34] and is likely to be the putative causal variant within the region. 35 The risk allele rs10993994-T is more common among populations of African ancestry (RAF AFR = 0.65, RAF AMR = 0.40, RAF EUR = 0.39) in Phase III 1KGP.…”
Section: Discussionmentioning
confidence: 99%